Implementation of international approaches to the accuracy evaluation methods in national practice of analytical research in soil science - Shovkovska А.V. (AgroChemistry and Soil Science, 2016)
There were analyzed the approaches to the evaluation of the accuracy of methods for determining the composition and properties of soil, established in national and harmonized standards of Ukraine. It was discovered lack of a single approach to estimation and ways of expressing precision methods in national standards of Ukraine. Given the results of the testing (according to requirements of DSTU GOST ISO 5725) accuracy (precision) methods for determination of phosphorus, potassium, organic matter and pH set the following standards: DSTU 4115, GOST 26483, DSTU 4289. Substantiated the advantages of using precision techniques for the evaluation approach regulated by international standards - DSTU GOST ISO 5725.